Prefectural System Practices in The Indonesian Local Government - Edy Sutrisno; Izzul Fatchu Reza; Nila Kurnia Wati; Elchin Gashimov (Universitas Muhammadiyah Yogyakarta, 2024)
This research aims to analyze the implementation of the prefectural system in Indonesia, examining its historical development, current application, and future trajectory in regional governance. This study employs a qualitative research design, utilizing a case study approach across several provinces in Indonesia. Data collection involved in-depth interviews, document analysis, and field observations to capture the nuances of the prefectural system's operation within different regional contexts. The prefectural system in Indonesia originated with the enactment of regional government laws and became more prominent after the New Order. It involves dividing the national territory into smaller administrative regions, with governors representing the central government, and features both deconcentration and decentralization. While previous studies have focused on decentralization and autonomy, this research highlights how these processes reinforce the prefectural system. This study provides fresh insights into the prefectural system's evolving role in Indonesia's decentralized governance. Unlike earlier works, it examines how the system balances central and local powers, anticipating its growing importance as Indonesia refines its decentralization policies.